Single cell analysis identified IFN signaling activation contributes to the pathogenesis of pediatric steroid-sensitive nephrotic syndrome - Qiu-Yu Li; Fei Liu; Xiaoyi Li; Minchao Kang; Linnan Bai; Tong Tong; Chen Zheng; Yanyan Jin; Xiaojing Zhang; Yi Xie; Dandan Tian; Yuanqing Pan; et al. (Biomarker Research)
Abstract Background Idiopathic nephrotic syndrome (INS) is a prevalent condition whose recurrence leads to multiple adverse effects. Previous studies on INS pathogenesis primarily focused on immune dysregulation, particularly T-cell changes and their correlation with cytokine shifts. Accumulating evidence suggests that B-cell dysfunction also plays a role. Nevertheless, a comprehensive understanding of the mechanisms and effective treatment strategies remains incomplete. Methods This study investigates changes in gene expressions and cellular interactions of immune cells at a single-cell level using peripheral blood mononuclear cells (PBMCs). And subsequently validated through quantitative PCR (qPCR), enzyme-linked immunosorbent assay (ELISA), and flow cytometry. Results We identified seven main clusters using unsupervised clustering of 103,213 high-quality single cells. Through unsupervised clustering, patient-specific T cells (IFI44L + CD4 + T cells) that exhibited a pronounced elevation of interferon-stimulated genes (ISGs) is identified. Activation of ISGs and interferon (IFN)-related pathways are also observed in other clusters. Specifically, this study demonstrates that interferon-γ (IFN-γ) plays a crucial role by promoting the interaction between B-cell activating factor (BAFF) and receptors on B cells. This interaction triggers the release of autoantibodies, thereby initiating INS pathogenesis. Furthermore, telitacicept has shown efficacy in treating pediatric patients with frequent relapse NS(FRNS). Conclusions Overall, our findings underscore the role of interferon and its related pathways in INS pathogenesis, providing novel therapeutic interventions for NS.